The effect of active sitting on trunk motion - Henry Wang; Kaitlyn J. Weiss; Mason C. Haggerty; Jacqueline E. Heath (Elsevier, 2014)
Background: Prolonged sitting is a risk factor for low-back pain. The primary purpose of this study is to determine if prolonged active sitting will result in increased trunk motion. Methods: Fifteen healthy female participants volunteered to sit for 30 min on each of three surfaces including an air-cushion, a stability ball, and a hard surface. Trunk motion was monitored using a Vicon motion capture system, and foot center of pressure was collected with two AMTI force plates. Results: Our findings indicated that the average speed of the trunk center of mass significantly increased with seating surface compliance. There were significant differences in right and left foot centers of pressure in the antero-posterior direction between the ball and air-cushion conditions and the ball and chair conditions. Conclusion: Active sitting results in increased trunk motion and could have a positive effect on low-back health.